Innovation and circular economy in the prison system: an analysis of the 10r’s - Veiga, Patricia Mayer; Sehnem, Simone; Crizel, Ana Cláudia Lara; Crizel, Marcelo Guerreiro; Mazzioni, Sady (Brazilian Journal of Production Engineering, 2025)
This study investigates the application of the 10R strategies as an innovation-driven alternative for advancing the circular economy in Santa Catarina state prisons. A qualitative single case study design was adopted, triangulating data from a systematic literature review, 16 semi-structured interviews with prison managers, and direct observation. Results show that despite some isolated sustainable practices, there is a lack of institutional coordination, stakeholder awareness, and technical training. Technological innovation, digital tools, and organizational routine redesign were identified as enablers of circularity. It is concluded that circular economy implementation requires a systemic approach with technological infrastructure and continuous engagement.